Pembinaan Tata Bahasa Indonesia Pada Administrasi Surat-Menyurat Dan Ruang Publik - Pujiatna, Tri; Mascita, Dede Endang; Gloriani, Yusida (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
The language of use, mostly Indonesian, in the general public (lay on the subject of Indonesian grammar) is not optimal. This happens because the rules of Indonesian language are not yet good and effective. These discrepancies are often found in all fields, such as public spaces and administrative institutions (correspondence). This needs to be understood. Therefore, efforts are needed to improve it. One way of coaching and socializing about the use of Indonesian. Efforts to foster and develop Indonesian language, both in their position as national languages and languages, need to be increased, before the global era and free trade era as it is today. This replaces the position and function of the Indonesian language to become more stable so that the Indonesian language can become a means of modern communication and be able to place itself parallel with other modern languages in the world. Through the Tri Dharma program of Higher Education, Community Service, the fostering and dissemination of Indonesian language aims to provide insight and understanding of the use of Indonesian language that is good and right. In addition, a language development and assistance program is provided by the Language Board of the Ministry of Education and Culture. This needs to be done so that people can prioritize the use of Indonesian